Smart Citizens in the Hackable City : On the Datafication, Playfulness, and Making of Urban Public Spaces Through Digital Art - de Lange, Michiel; Synnes, Kåre; Leindecker, Gerald (Luleå tekniska universitet, Datavetenskap, 2019)
This contribution explores concepts, approaches and technologies used to make urban public spaces more playful and artful. Through a variety of compelling narratives involving play and art it assists in the design of new cyberparks, public spaces where digitally mediated interactions are an inherent part. How can play and interactive art be used to strengthen urban public spaces by fostering citizen engagement and participation? We propose to not only utilise interactive media for designing urban (public) spaces, but also for social innovation for the benefit of citizens. in cyberparks. The contribution connects urbanity, play and games, as well as concepts of active and passive interactive digital art as part of trends towards pervasive urban interaction, gameful design and artification. We position this as an important part of developing human-centred smart cities where social capital is central, and where citizens engaging in play and art are prerequisites for sustainable communities. Using art, play and games to foster citizen engagement and collaboration is a means to develop social technologies and support the development of collective intelligence in cyberparks. This is studied in concrete cases, such as the Ice Castle in Luleå, Sweden and the Ars Electronica in Linz, from a multi-disciplinary stance involving interaction design, digital art, landscape design, architecture, and health proficiencies. We will analyse two cases of gameful design and one case of digital interactive art being used to address urban issues. Rezone the game is an interactive multimedia game developed to tackle vacancy in the city of Den Bosch in the Netherlands. The Neighbourhood is a board game developed to involve various stakeholders in making their neighbourhood using water as a collective resource. CyberParks